Adsorption removal of colistin from aqueous solution using NaOH-modified granular activated carbon - Thaiboonrod, Sineenat; Hanwarinroj, Chayanin; Smata, Attajaree; Kanarat, Areerat; Thanayupong, Eknarin; Ngammuangtueng, Pitak; Banjerdkij, Peerakarn; Chaleawlert-umpon, Saowaluk; Pimpha, Nuttaporn (Bulletin of Applied Sciences, 2024)
Nowadays, antibiotic contamination in water sources is increasingly being detected, contributing to the rise of the causes of drug resistance. Colistin is a last-resort antibiotic used to treat infections that are resistant to other antibiotics in both humans and animals. However, it is not completely adsorbed by both human and animal bodies, leading to its excretion and subsequent environmental contamination. This research studies the use of sodium hydroxide modified granular activated carbon (m-GAC), prepared by a simple and low temperature activation process for the adsorption of colistin in water. Batch adsorption experiment was investigated at a colistin concentration of 250 mg/L. The maximum adsorption capacity of the m-GAC was significantly higher (83.9 mg/g) than the unmodified activated carbon (GAC, 31 mg/g). The adsorption behavior matched well with the Freundlich isotherm, and the pseudo-second-order kinetic model. Additionally, the m-GAC exhibited a higher rate of colistin absorption compared to GAC. The predominant adsorption mechanisms are likely a strong physical adsorption, including electrostatic attraction and hydrogen bonding. The increase in oxygen-containing groups on the surface of m-GAC enhances its adsorption efficiency. This study offers foundational insights for improving the adsorption efficiency of activated carbon on a scalable production level for colistin removal application in water and further aiding in the control of colistin resistance-spread among microorganisms.